Reduced microRNA-150 is associated with poor survival in pulmonary arterial hypertension. - Rhodes,CJ; Wharton,J; Boon,RA; Roexe,T; Tsang,H; Wojciak-Stothard,B; Chakrabarti,A; Howard,LS; Gibbs,JS; Lawrie,A; Condliffe,R; Elliot,CA; et al. (American Journal of Respiratory and Critical Care Medicine, 2013)
MicroRNAs (miRNAs or miRs) are implicated in the pathogenesis of various cardiovascular diseases, including pulmonary arterial hypertension (PAH).